Molecular Study of IL-7R Gene Polymorphism and their Associations with Male Multiple Sclerosis Patients in Erbil Province. - Shukur W. Smail (Zanco Journal of Pure and Applied Sciences, 2021)
Multiple sclerosis (MS) is an autoimmune disease in which immune cells attacks the body cells mistakenly; it is characterized by chronic inflammation that leads to demyelination and conduction of nerve impulse is affected negatively. The cause of the disease is unknown, but it may be partially under the control of genetics, including interleukin 7 receptor alpha (IL7Rα). In this case-control study, 40 relapsing-remitting MS (RRMS) male patients, which fulfills McDonald criteria and 40 healthy controls, with matched sex, were compared depending on the rs6897932 polymorphism within the exon 6 of IL7Rα gene by Tetra-amplification refractory mutation system polymerase chain reaction (Tetra-ARMS-PCR) method. The frequency of T allele of IL7Rα rs6897932 was considerably higher in male MS patients than healthy control males (31.25 vs 17.5%). Genotype distributions of the single nucleotide polymorphism (SNP) rs6897932 deviated from Hardy-Weinberg equilibrium with a p-value of 0.80. Both homozygous (TT) and Heterozygous (CT) were non-significantly positively associated with MS male patients (OR = 6.75, 95%CI = 0.73-62.4, p = 0.059, OR = 1.68, 95%CI = 0.64-4.38, p = 0.28) respectively. The distribution of the rs6897932 polymorphism is not significantly different in our case/control study in the Erbil province.